Repcebecő-ormányos Ceutorhynchus obstrictus (Coleoptera: Curculionidae) imágókon végzett piretroid (lambda-cihalotrin) rezisztencia vizsgálat - Gombai, Balázs; Szántóné Veszelka, Mária; Farkas, István; Havasréti, Béla; Hegedűsné Baranyai, Nóra; Marczali, Zsolt (GEORGIKON FOR AGRICULTURE, 2017)
One of the most important pests of the winter oilseed rape is cabbage seed weevils. We used IRAC 31 method pyrethroid resistance test with lambda-cyhalotrin on the collected beetles from four different places of Hungary. According to our examination the tested beetles were in susceptible category because the mortality on 0,015 µg/cm² dose was 100%. In case of the lowest dose on 0,003 µg/cm2 we experienced significant mortality.
Keywords: Ceutorhynchus obstrictus; resistance; IRAC; pyrethroid